The Effect Of Sex-Linked Dwarf (Dw), Naked Neck (Na) And Frizzle (F) Genes On Various Traits In Laying Hens Under Tropical Conditions - Hj. Idrus, Zulkifli (1991)

(untitled)
A study was carried out to investigate the effect of the sex-linked dwarf (dw) , naked neck (Na) and frizzle (l) genes on various quantitative traits in layers and also to identify the appropriate genotypes under tropical conditions . The experimental stock comprised of non-dwarf non-frizzled non-naked neck or normal (Dw- ff nana) , naked neck (Dw- ff Nana) , frizzled (Dw- Ff nana) , frizzled naked neck (Dw- Ff Nana) , dwarf (dw- ff nana) , dwarf naked neck (dw- ff Nana) , dwarf frizzled (dw- Ff nana) and dwarf f rizzled naked neck (dw- Ff Nana) genotypes . The dw was observed to cause a profound reduction in body weight , body conformation , egg production and egg weight . However , the dw reduced feed intake and improved feed efficiency . The dw also had detrimental effect on several egg quality traits. Body weight and body conformation measurements were not affected by the Na , while feed intake was significantly increased in both dwarf and non-dwarf populations . The Dw- ff Nana hens were observed to have better egg production and egg weight . Shell quality traits were found to improve due to the Na . However , among the dwarf population , the Na had an adverse effect on feed efficiency.